Philogenia gaiae sp. nov. (Zygoptera: Philogeniidae) and description of the female of P. macuma Dunkle, 1986, two species from the Ecuadorean lowland rainforest - Vilela, Diogo Silva; Guillermo-Ferreira, Rhainer; Encalada, Andrea C.; Cordero-Rivera, Adolfo (Zootaxa, 2019)
Philogenia gaiae sp. nov. (Holotype ♂, Ecuador, Orellana, Tiputini Biodiversity Station, -0.6349, -76.1501, 241 m, 13 xii 2012, A. Cordero-Rivera & M. Sánchez-Herrera leg., in MUAE) from the helena group is described, illustrated, diagnosed and compared with morphologically close species of the genus. Philogenia gaiae can be distinguished from its most similar congener P. minteri Dunkle, 1986 by the enlarged cerci and the club-like paraprocts. We also describe the female of P. macuma Dunkle, 1986, from a pair collected at Jatún Sacha Biological Reserve, which is also similar to P. gaiae and can be distinguished by the intersternite morphology, ovipositor length and vulvar lamina shape.